2021
DOI: 10.1371/journal.pone.0248777
|View full text |Cite
|
Sign up to set email alerts
|

Sulforaphane (SFA) protects neuronal cells from oxygen & glucose deprivation (OGD)

Abstract: Background Perinatal brain injury results in neurodevelopmental disabilities (neuroDDs) that include cerebral palsy, autism, attention deficit disorder, epilepsy, learning disabilities and others. Commonly, injury occurs when placental circulation, that is responsible for transporting nutrients and oxygen to the fetus, is compromised. Placental insufficiency (PI) is a reduced supply of blood and oxygen to the fetus and results in a hypoxic-ischemic (HI) environment. A significant HI state in-utero leads to per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 40 publications
1
4
0
Order By: Relevance
“…This fact indicates that the results obtained in biochemical tests, as well as in experiments in the T-maze, are stipulated precisely by the change in the concentration of deuterium. This is also consistent with the results of experiments on cerebellar cell cultures, which showed that placing neurons in a medium containing δ 2 H equal to −357‰ increases their resistance to glucose deprivation, which was used to model pathological processes in cerebral ischemia [ 66 , 67 ]. In this case, the response of cultured neurons is generally comparable to the response of brain cells in vivo, when intensification of free radicals’ synthesis, lipid peroxidation, and changes in the activity of antioxidant enzymes are observed [ 68 , 69 ].…”
Section: Discussionsupporting
confidence: 87%
“…This fact indicates that the results obtained in biochemical tests, as well as in experiments in the T-maze, are stipulated precisely by the change in the concentration of deuterium. This is also consistent with the results of experiments on cerebellar cell cultures, which showed that placing neurons in a medium containing δ 2 H equal to −357‰ increases their resistance to glucose deprivation, which was used to model pathological processes in cerebral ischemia [ 66 , 67 ]. In this case, the response of cultured neurons is generally comparable to the response of brain cells in vivo, when intensification of free radicals’ synthesis, lipid peroxidation, and changes in the activity of antioxidant enzymes are observed [ 68 , 69 ].…”
Section: Discussionsupporting
confidence: 87%
“…Nrf2 activator can upregulate the expression of antioxidant protein and scavenge ROS. After activation, Nrf2 reduces the maturation and expression of inflammatory factors such as interleukin-1 β (IL-1 β ), tumor necrosis factor- α (TNF- α ), and IL-18 to inhibit the inflammatory response after cerebral I/R injury [ 40 , 41 ]. Under physiological conditions, Nrf2 exists in the cytoplasm and Keap1 protein anchors Nrf2 to the cytoskeleton of actin, preventing Nrf2 from entering the nucleus to exert its transcriptional activity.…”
Section: Discussionmentioning
confidence: 99%
“…Neuroprotection refers to the mechanisms and strategies used to defend the central nervous system (CNS) (Figure 3) against injury due to both acute (e.g., trauma or stroke) and chronic neurodegenerative disorders (e.g., dementia, Parkinson's, Alzheimer's, epilepsy) [13]; by extension, neuroprotective agents comprise a category of agents that generally are used to protect neuronal structure and/or function. Research on the neuroprotective effects of SFN began in 2004 with studies that showed its effects protecting neurons [14] and microglia [15] against oxidative stress via activation of nuclear factor erythroid 2-related factor 2 (Nrf2). The research literature is replete with studies that support the vital role played by the Nrf2 pathway in the neuroprotective effects of SFN [14,[16][17][18][19][20][21], evidenced by lack of neuroprotection from toxins in Nrf2-knockout mice treated with SFN [22,23].…”
Section: Sfn As a Neuroprotective Agentmentioning
confidence: 99%
“…Research on the neuroprotective effects of SFN began in 2004 with studies that showed its effects protecting neurons [14] and microglia [15] against oxidative stress via activation of nuclear factor erythroid 2-related factor 2 (Nrf2). The research literature is replete with studies that support the vital role played by the Nrf2 pathway in the neuroprotective effects of SFN [14,[16][17][18][19][20][21], evidenced by lack of neuroprotection from toxins in Nrf2-knockout mice treated with SFN [22,23]. In a study of Parkinson's disease that used a 6-hydroxydopamine-Parkinson's disease mouse model, treatment of SH-SY5Y cells with SFN was found to have a protective effect on the neurons, which was attributed to the observed increases in active nuclear Nrf2 protein, Nrf2 mRNA, and total glutathione levels and inhibition of neuronal tissue apoptosis [24].…”
Section: Sfn As a Neuroprotective Agentmentioning
confidence: 99%